Developing composite of ZE41 magnesium alloy- calcium by friction stir processing for biodegradable implant applications. (2019) - Vasu, Ch.; Naga Durga, K.J.A.; Srinivas, I.; Dariyavali, Shaik; Venkateswarlu, B.; Ratna Sunil, B.
Abstract: In the present work, ZE41Mg alloy - Ca composite was produced by friction stir processing (FSP) targeted for biodegradable implant applications. Microstructural studies revealed grain refinement in the composite as 7 µm from a starting size of 110 µm. Due to grain refinement, increased hardness was observed in the composite. Degradation behavior was analyzed by immersion method conducted in Ringers physiological solution for 168 h. From the immersion studies, it was a clear observation that the degradation rate of composite has been decreased with increase in the immersion time compare with unprocessed ZE41. pH measurements and also surface phase and morphology analysis done by X-Ray diffractometry (XRD) and scanning electron microscopy (SEM) respectively, revealed that the corrosion behavior was better for the composite compared with the unprocessed ZE41. The promising behavior of the composite can be attributed to the grain refinement, texture effect and the presence of Ca which decreased the formation of magnesium hydroxide and promoted better corrosion resistance. Hence from the preliminary results, it can be understood that ZE41-Ca composites can be successfully produced by FSP targeted for degradable implant applications with controlled degradation rate without deteriorating the mechanical properties.